Bioottisten interaktioiden merkitys ympäristögradienteilla : Esimerkkinä variksenmarjan vaikutus arktis-alpiinisessa kasvillisuudessa - Mod, Heidi (Helsingfors universitet, 2012)
Plant-plant interactions, i.e. biotic interactions, shape plant communities and the vegetation's succession along abiotic environmental factors. Positive interactions (e.g. facilitation) may expand species niches and enhance growth and reproduction. Negative interactions (e.g. competition, allelopathy) can interfere with growth and reproduction, even out competing some species from their niches. Negative and positive interactions co-occur, but research has shown that positive interactions are generally more common and important than negative ones in harsh environments. The theory of change of net-interaction from negative to positive along an environmental gradient is called the stress gradient hypothesis (=SGH). This work examines nordic crowberry's (Empetrum nigrum ssp. hermaphroditum) effect on arctic-alpine species' sexual reproduction under different environmental stress levels. Crowberry is a dominant species in low-nutrient, acidic arctic-alpine ecosystems. Its competitive ability is based on allelopathic characteristics and a forming of dense mats. It is also unpalatable for herbivores. The species facilitative characteristics include providing shelter from the wind and maintaining an ericoidmycorrhiza community. In this research environmental stress is represented by geomorphological disturbance and soil moisture, with the interactions between crowberry and other species are examined as the relationship between crowberry cover and the fitness measures (e.g. abundance of flowers or fruits) of study species. Explanation for the variation in the effects of crowberry is tried to find from the traits of the study species. Data was collected in May 2011 from Kilpisjärvi, northernmost Finland. The study area comprised 960 1m2 cells. In each cell the cover of each species (including crowberry), the abundance of each species flowers or fruits, the cover of geomorfological disturbance and soil moisture were recorded. Generalized linear models (=GLM) were run for all species to identify the best model for ...